Engineering Cytochrome P450 BM-3 for Oxidation of Polycyclic Aromatic Hydrocarbons - Li, Qing-Shan (American Society for Microbiology, 2001)
Cytochrome P450 BM-3, a self-sufficient P450 enzyme from Bacillus megaterium that catalyzes the subterminal hydroxylation of long-chain fatty acids, has been engineered into a catalyst for the oxidation of polycyclic aromatic hydrocarbons. The activities of a triplet mutant (A74G/F87V/L188Q) towards naphthalene, fluorene, acenaphthene, acenaphthylene, and 9-methylanthracene were 160, 53, 109, 287, and 22/min, respectively. Compared with the activities of the wild type towards these polycyclic aromatic hydrocarbons, those of the mutant were improved by up to 4 orders of magnitude. The coupling efficiencies of the mutant towards naphthalene, fluorene, acenaphthene, acenaphthylene, and 9-methylanthracene were 11, 26, 5.4, 15, and 3.2%, respectively, which were also improved several to hundreds fold. The high activities of the mutant towards polycyclic aromatic hydrocarbons indicate the potential of engineering P450 BM-3 for the biodegradation of these compounds in the environment.